Effectiveness of export incentives in Malaysia - Ahmad, Sa'ari; Ahmad, Fais; Ahmad Fawzi, Dzulhilmi (2016)
The empirical results presented in this report focused on Malaysian government export incentives for small and medium-sized enterprises (SMEs) involved in exports activities. More specifically, the study attempts to examine the relationships between export incentives and the increased in export activities of the SME’s . The data was collected through 5000 mail questionnaires sent to the selected SMEs. Three hundred firms responded by returning the questionnaires.Only 250 were fully completed used in the analysis.The findings clearly indicates that : export activities of SMEs were differentiated by the export incentives which was based on the age of the company, export destination, double deduction for promotion of Malaysian Brands , double deduction for promotion of Exports of services.